Thermal Transport in Semiconductors First Principles and Phonon Hydrodynamics - Torres Alvarez, Pol (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
Starting from a broad overview of heat transport based on the Boltzmann Transport Equation, this book presents a comprehensive analysis of heat transport in bulk and nanomaterials based on a kinetic-collective model (KCM). This has become key to understanding the field of thermal transport in semiconductors, and represents an important stride. The book describes how heat transport becomes hydrodynamic at the nanoscale, propagating very much like a viscous fluid and manifesting vorticity and friction-like behavior. It introduces a generalization of Fourier's law including a hydrodynamic term based on collective behavior in the phonon ensemble. This approach makes it possible to describe in a unifying way recent experiments that had to resort to unphysical assumptions in order to uphold the validity of Fourier's law, demonstrating that hydrodynamic heat transport is a pervasive type of behavior in semiconductors at reduced scales. .